Modeling and Optimization of Service Investigation Services: Empirical Study Using Pop-Hrm Approach at Head of Private Smk School in Bogor District, Indonesia - Andi Hermawan; A. Muwahid Muhammadi; Briliantina Indrati (The Institute of Academic Research and Publication (IARP), 2023)
The Head of School as head of the school is a contributing factor to success in efforts to strengthen governance, accountability, and public image. This success is not independent of competence and ability in tasks, roles, and functions. Providing primary service to all school citizens, optimizing the empowerment and development of the school citizen, focusing on performance and growth, and impacting school progress and society, this leadership is called serving leadership. Based on preliminary research, it is known that the head of a private SMK school in the Bogor district has not optimally demonstrated serving leadership. This research aims to produce ways and strategies for strengthening leadership serves by analyzing the influence of positive and dominant influence variables on serving leadership. The research uses the POP-HRM approach (Modeling and Management Resource Enhancement Optimization) with SITOREM analysis to produce optimal solutions from existing solutions. Implications of the research are, that if serving leadership wants to be empowered then it requires the development of adversity intelligence, proactive personality, teamwork, and increased commitment to the organization, as well as work motivation.